Melanoma maligno cutáneo en una mujer indígena del municipio de Alto Baudó, Chocó, Colombia (2014)
Cutaneous malignant melanoma is a deadly disease, which in recent years has spread worldwide, is an entity that affects the skin and organs that origínate from the neural crest during embryonic development. The history of melanoma is summarized in the growth and local invasion of the skin, and the development of it, influence of both environmental and genetic factors. This condition is uncommon in breed types, such as African and indigenous descent, therefore because of this particular event, the aim of this paper is to demonstrate through an observational analytic study, a case of an indigenous, natural woman Alto Baudó, Choco Colombia, who during the time of treatment, is diagnosed with cutaneous malignant melanoma. Currently this disease has many standard treatment options, but still, the patient’s family under study, reject any surgical procedure to counteract the disease, because for them it is more important beliefs of the indigenous reserves, knowing in advance, a premature opinion with appropriate treatment, are essential to neutralize the disease in time, unfortunately in these indigenous cultures, their beliefs more raw, the patient’s right to a dignified life. (MED. UIS. 2014;27(1):59-68)